2021
DOI: 10.3390/jpm11060558
|View full text |Cite
|
Sign up to set email alerts
|

Severe COVID-19 in Hospitalized Carriers of Single CFTR Pathogenic Variants

Abstract: The clinical presentation of COVID-19 is extremely heterogeneous, ranging from asymptomatic to severely ill patients. Thus, host genetic factors may be involved in determining disease presentation and progression. Given that carriers of single cystic fibrosis (CF)-causing variants of the CFTR gene—CF-carriers—are more susceptible to respiratory tract infections, our aim was to determine their likelihood of undergoing severe COVID-19. We implemented a cohort study of 874 individuals diagnosed with COVID-19, dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 49 publications
4
18
0
Order By: Relevance
“…Yet, other studies have brought supporting evidence for the implication of type I IFN-independent genes as monogenic etiologies of COVID-19. For example, genetic variants in the CFTR gene, including those causing cystic fibrosis, have been found to be overrepresented among critically ill COVID-19 patients [ 18 20 ], consistent with previous associations of the gene with susceptibility to respiratory tract infections [ 21 ]. Likewise, a genetic polymorphism in the androgen receptor ( AR ) gene that correlates with low serum testosterone level has been associated with severe COVID-19 in men [ 22 ].…”
Section: Monogenic Predisposition To Covid-19supporting
confidence: 77%
“…Yet, other studies have brought supporting evidence for the implication of type I IFN-independent genes as monogenic etiologies of COVID-19. For example, genetic variants in the CFTR gene, including those causing cystic fibrosis, have been found to be overrepresented among critically ill COVID-19 patients [ 18 20 ], consistent with previous associations of the gene with susceptibility to respiratory tract infections [ 21 ]. Likewise, a genetic polymorphism in the androgen receptor ( AR ) gene that correlates with low serum testosterone level has been associated with severe COVID-19 in men [ 22 ].…”
Section: Monogenic Predisposition To Covid-19supporting
confidence: 77%
“…Yet the recent GEN-COVID multicenter trial showed that non-pregnant CF carriers (heterozygous) are predisposed to severe COVID-19 and a higher risk of death. The authors also noted previous studies suggesting that active CF patients (homozygous) appeared to undergo a mild form of COVID-19 and postulate this discrepancy could be due to their treatment with CFTR modulators while the CF carriers (heterozygous) are not treated [ 11 ].…”
Section: Discussionmentioning
confidence: 58%
“…Thus, whether the risk of developing severe COVID-19 is increased in pwCF because of their P. aeruginosa infection remains unresolved and will require further meta-analysis performed using international cohorts. Moreover, a recent study including 874 individuals with COVID-19 showed that carriers of CF-causing variants (N=40) may be more likely to develop severe COVID-19 ( 38 ). This reinforces the interest in studying the specific role of CFTR in the pathogenesis of COVID-19.…”
Section: Discussionmentioning
confidence: 99%